ULTRADISPERSE FERROMAGNETIS IN SOFT POLYMERS: MAGNETIC CONTROL OVER INTERNAL STRUCTURE AND MACROSCOPIC DEFORMATIONS - Raikher, Yu.L.; Stolbov, O.V.; Biller, A.M. (Perm Federal Research Centre Journal, 2016)
Magnetorheological elastomers (MREs) are dispersions of magnetically soft ferromagnets (particle size of units of microns) in high-elasticity matrices. Such composites, responding intensely to an applied field, demonstrate a number of unique properties (powerful magnetostiction, the effect of magnetic shape memory) that make them very attractive for practical use. The structural changes, occurring at the mesoscopic level, are the key functionality of MREs, that is at the reference scale of the particle size and interparticle distances. These processes take place under the influence of two major factors: the magnetic forces striving to regroup the particles and the elastic stresses, generated by the matrix in response to that. In the present paper we study magnetomechanics of a model representing element of a MRE, that is a pair of particles embedded in an elastic medium. For the first time, the consideration is free of a number of unjustified simplifications, which are yet widely used in the literature. Namely, (i) the magnetization law is taken in its nonlinear form. (ii) the particles are treated as finite-size objects, (iii) the physical nonlinearity of the elastomer elasticity is taken into account, (iv) the equations of equilibrium are written down in terms of the finite-deformation theory. Our investigation demonstrates that magnetization of the MRE element causes its bistability (a regime with two stable states). As a consequence, the particles collapse on each other (form a pair cluster) and its transformation goes via hysteresis scenario. The occurrence of magnetomechanical hysteresis at the mesoscopic level, delivers a natural explanation for the magneto-induced plasticity (magnetic shape memory effect) that is observed experimentally in macroscopic samples of MREs.